Policy analysis in the twenty-first century Complexity, conflict and cases - Radin, Beryl A. (Routledge, 2019)
The field called policy analysis focused originally on the formulation of new policies and was structured to give advice to those in the top reaches of government agencies. Within several decades the field moved beyond the formulation stage of the policy process (creating new policies) to agenda setting, implementation, and evaluation of existing policies. New skill sets emerged and staff were found in many parts of the policy world. Despite these changes, there has been little attention paid to the possible shifts in the relationship between analysts and clients, and students of policy analysis often enter the world of work with little exposure to the situations they might face. Policy Analysis in the Twenty-First Century is designed to familiarize students with the diversity of experiences that they can expect to face in their practitioner role.